Musyawarah Perencanaan Pembangunan dengan Optimalisasi Evidence Based Policy Kasus Penurunan Kemiskinan - Noor Rizky Tiara Putri; Najua Febrian Rachmawati; Abinaya Fikri Nayotama; Prianda Defri Harmansyah (Jurnal Kapita Sosial Politik, 2024)
Poverty is one of the problems in Indonesia that can be categorized as chronic and never ending. Dynamic human development adds to the complexity of poverty. To answer these problems, development planning meetings exist as a forum for community aspirations in voicing problems. This study uses a qualitative descriptive method with a literature review approach. The results of the study show that deliberations on development planning are one of the ways to find evidence that is used as the basis for making evidence-based policies.